Simulation debriefing and the development of clinical judgement of student nurses at a University in Gauteng - Dubula, Mapule Pamella (My University, 2018)
Background: There are limited learning opportunities available for students in the clinical settings due to the reduction in the length of patient hospital stays, the shortage of clinical educators and increasing number of students competing for clinical learning opportunities. Simulation-based learning is an innovative way of replicating the real-life clinical scenarios in the nursing school setting. Clinical simulation includes prebriefing, simulation action, and debriefing phases. Debriefing is a critical component of simulation-based learning because most knowledge is gained during that phase. Objective: This study sought to assess the effect of debriefing on the development of clinical judgement in second and fourth-year nursing students in a university in Gauteng. Methods: A one group pre-test/ post-test quasi-experimental design was utilized in this study. Ethical clearance was obtained from the university’s Human Research Ethics Committee. 60 out of the 64, second and fourth year students consented to participate in the study. Only 56 out of the 60 consenting students completed the self-administered pre and post-test Lasater Clinical Judgement Rubrics. Results: The data were analysed quantitatively using descriptive and inferential statistics. The mean difference between the post- and pre-tests is 3.267857 at 95% confident interval. There was a significant improvement in the level of clinical judgement after debriefing (p-value=0.000006421). The results have also shown that debriefing improved clinical judgement among the 4th more than the 2nd years (2nd-year p-value 0.00305, 4th-year p-value 0.0004326) Conclusion: Debriefing is a critical element of simulation for the development of clinical judgement as it gives the students the opportunity to reflect on their thoughts and actions during the simulation action, and plan for improvement.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirement for the degree of Master of Science in Nursing. Johannesburg, 2018.
Keywords: Clinical Judgement; Clinical Simulation; Students, Nursing